Cyber Sexual Harassment pada Cosplayer Perempuan di Media Sosial Tahun 2023 - Oryza Satifa; Neri Widya Ramailis (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2025)
The purpose of this study was to find out what causes women to experience cyber sexual harassment in cyberspace, especially cosplayers. The research method is a visual criminology method, while the research subjects themselves are women who cosplay at X who have received cyber sexual harassment. The results of this study are that women who cosplay at X throughout 2023 received harassing comments either in the replay column or on third-party websites such as secreto, retrospring, and others. Victims feel unsafe and uncomfortable receiving harassing comments on the photos they upload. It can be concluded that from a victimology perspective, cyber sexual harassment can occur to victims even though the victim does not know the perpetrator. Victims can also become victims when the victim does not suspect that their actions can encourage the perpetrator to do evil to them even though they have not specifically done anything to the criminal. The use of social media can encourage anyone to become a victim because of the low awareness of the actions taken by the perpetrator making the victim feel uncomfortable. Keywords: Cosplayer, Cyber Sexual Harassment, Social Media, Victimology.